Cationic Porphyrins as Effective Agents in Photodynamic Inactivation of Opportunistic Plumbing Pathogen Legionella pneumophila - Andrija Lesar (International Journal of Molecular Sciences, 2020)
Legionella pneumophila is an environmental bacterium, an opportunistic premise plumbing pathogen that causes the Legionnaires’ disease. L. pneumophila presents a serious health hazard in building water systems, due to its high resistance to standard water disinfection methods. Our aim was to study the use of photodynamic inactivation (PDI) against Legionella. We investigated and compared the photobactericidal potential of five cationic dyes. We tested toluidine blue (TBO) and methylene blue (MB), and three 3-N-methylpyridylporphyrins, one tetra-cationic and two tri-cationic, one with a short (CH3) and the other with a long (C17H35) alkyl chain, against L. pneumophila in tap water and after irradiation with violet light. All tested dyes demonstrated a certain dark toxicity against L. pneumophila; porphyrins with lower minimal effective concentration (MEC) values than TBO and MB. Nanomolar MEC values, significantly lower than with TBO and MB, were obtained with all three porphyrins in PDI experiments, with amphiphilic porphyrin demonstrating the highest PDI activity. All tested dyes showed increasing PDI with longer irradiation (0–108 J/cm2), especially the two hydrophilic porphyrins. All three porphyrins caused significant changes in cell membrane permeability after irradiation and L. pneumophila, co-cultivated with Acanthamoeba castellanii after treatment with all three porphyrins and irradiation, did not recover in amoeba. We believe our results indicate the considerable potential of cationic porphyrins as effective anti-Legionella agents.